A survey of plants and plant products traditionally used in livestock health management in Buuri district, Meru County, Kenya - Gakuubi Martin; Wanzala Wycliffe (BMC, 2012)
Abstract Background Up till now, nomadic communities in Africa have been the primary focus of ethnoveterinary research. Although mainly arable and/or mixed arable/pastoral farmers, Ameru of central Kenya are known to have a rich history of ethnoveterinary knowledge. Their collective and accumulative ethnoveterinary knowledge (EVK) is likely to be just as rich and worth documenting. The aim of the study was to document and analyse the ethnoveterinary knowledge of the Ameru. Methods Non-alienating, dialogic, participatory action research (PAR) and participatory rural appraisal (PRA) approaches involving 21 women and men aged between 50 and 79 years old were utilized. A combination of snowball and purposive sampling methods were used to select 21 key respondents. The methods comprised a set of triangulation approach needed in EVK for non-experimental validation of ethnoknowledge of the Ameru. Results A total of 48 plant species distributed in 26 families were documented with details of diseases/ill-health conditions, parts of plants used and form of preparation and administration methods applied to different animal groups. Of these families, Fabaceae had the highest number of species (16.67%), followed by Solanaceae (12.5%), Asteraceae and Euphorbiacea (each comprising 8.33%), Lamiaceae (6.25%), Apocynaceae and Boraginaceae (each comprising 4.17%), while the rest of the 19 families, each was represented by a single plant species. About 30 livestock diseases/ill-health conditions were described, each treated by at least one of the 48 plant species. Most prevalent diseases/ill-health conditions included: - anaplasmosis, diarrhea, East Coast fever, pneumonia, helminthiasis, general weakness and skin diseases involving wounds caused by ectoparasites. Conclusion The study showed that there was a rich knowledge and ethnopractices for traditional animal healthcare amongst the Ameru. This study therefore provides some groundwork for elucidating the efficacy of some of these plants, plant products and ethnopractices in managing livestock health as further research may lead to discovery of useful ethnopharmaceutical agents applicable in livestock industry.